2016
DOI: 10.1016/j.ygcen.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and manipulation of reproductive cycles in the jaguar (Panthera onca)

Abstract: Basic reproductive information in female jaguars (Panthera onca) is lacking, thus longitudinal fecal samples from seven females were analyzed via enzyme immunoassay to measure estradiol and progestin metabolites throughout the year. Mean estrus length of 194 estrus periods measured hormonally was 6.5±0.3d, mean peak fecal estradiol concentration was 138.7±5.7ng/g; and in one female, estrus resumption occurred approximately 15d post-partum. Ovulation, as indicted by sustained elevated progestin concentrations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 56 publications
(68 reference statements)
0
7
0
1
Order By: Relevance
“…A more recent study by Barnes et al (2015) characterized and manipulated the reproductive cycles in female jaguars showing spontaneous ovulation in this species, and multiple estrous cycles throughout the year and no notable seasonality. [5]. The hormonal characterization of the reproductive cycles of females has been conducted using noninvasive longitudinal monitoring techniques in feces of different species of felids in captivity, including the jaguar [4,5], lions (Panthera leo), tigers (Panthera tigris), caracals (Caracal caracal), cheetahs (Acinonyx jubatus), and domestic cats (Felis catus) [13] to evaluate hypophysis-gonad function in lions roaming free in the Serengeti savannah and in the crater of the Ngorongoro [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent study by Barnes et al (2015) characterized and manipulated the reproductive cycles in female jaguars showing spontaneous ovulation in this species, and multiple estrous cycles throughout the year and no notable seasonality. [5]. The hormonal characterization of the reproductive cycles of females has been conducted using noninvasive longitudinal monitoring techniques in feces of different species of felids in captivity, including the jaguar [4,5], lions (Panthera leo), tigers (Panthera tigris), caracals (Caracal caracal), cheetahs (Acinonyx jubatus), and domestic cats (Felis catus) [13] to evaluate hypophysis-gonad function in lions roaming free in the Serengeti savannah and in the crater of the Ngorongoro [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[5]. The hormonal characterization of the reproductive cycles of females has been conducted using noninvasive longitudinal monitoring techniques in feces of different species of felids in captivity, including the jaguar [4,5], lions (Panthera leo), tigers (Panthera tigris), caracals (Caracal caracal), cheetahs (Acinonyx jubatus), and domestic cats (Felis catus) [13] to evaluate hypophysis-gonad function in lions roaming free in the Serengeti savannah and in the crater of the Ngorongoro [14,15]. These noninvasive techniques permit learning about the physiological reproductive condition of animals found in zoological collections, with minimal human intervention, thus lowering animal stress and maintaining their well-being [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observable signs are vocalizations in the form of grunts, calling the male, rubbing against inanimate objects, lordosis, rolling on the ground, the female allows the male to sniff the vulva and accommodates it in order to perform the mating (Yescas and Ramírez, 2013). It has been reported that the mean estrous duration of 194 hormonally measured estrous periods in seven females was 6.50.3 d (Barnes et al, 2016). Oestrus: in this phase, fertilization is likely to occur, corpora lutea will develop and there will be progesterone secretion to maintain gestation.…”
Section: Estrous Cyclementioning
confidence: 99%
“…Lab C analyzed fecal extracts using a monoclonal progesterone antibody (mono-P4: Quidel clone 425), a polyclonal progesterone antibody (poly-P4: R4859), a pregnanediol antibody (PdG: pregnanediol-3-glucuronide, R13904) and an estrogen metabolite antibody (E2c: estradiol 17 R0008), all developed by Coralie Munro, University of California, Davis, CA, USA. A double-antibody EIA protocol was used as previously described [18,23]. The intraand inter-assay coefficients of variation for all assays were < 10% (average 2.58%) and < 20% (average 8.07%), respectively.…”
Section: Enzyme Immunoassays (Eias) and Validationmentioning
confidence: 99%